DAMPAK COVID-19 TERHADAP UMKM DI DAERAH ISTIMEWA YOGYAKARTA DAN IDE UNTUK MENGHIDUPKAN KEMBALI EKONOMI - Ali Ridlo (Kopertais Wilayah III Yogyakarta, 2022)
Absract This paper was created with the aim of evaluating the profound impact of Covid-19 on micro, small and medium enterprises (MSMEs) as well as to illustrate certain effective ideas for reviving the economy. The type of research used by researchers in this study is to use a qualitative descriptive method approach. The time interval for the research study is from January 2020 to November 2020. This research is limited to the Special Region of Yogyakarta. The results of this study are the impact of the Covid-19 pandemic on MSME businesses operating in the Special Region of Yogyakarta, namely the availability of limited raw materials, the price of the main raw materials has increased, production capacity has decreased, business marketing has decreased, sales partners have decided to stop purchasing products, labor laid off, export demand declined, had loans, and had problems repaying loans. Mitigation measures taken by the government to revitalize the economy are government policies on raw materials and marketing of MSMEs. The best innovative ideas to help the MSME industry recover faster include (1) raw materials, namely looking for alternative raw material suppliers, looking for alternative raw materials, looking for alternative raw material suppliers. (2) The production process is making product innovations. (3) marketing, namely looking for alternative marketing partners, optimizing digital marketing. (4) workforce, namely facilitating personal protective equipment so that employees continue to work. Keywords: Micro, Small and Medium Enterprises (MSMEs), Innovation, Industry, Mitigating Measures